The Penderwicks at Point Mouette - Birdsall, Jeanne (New York : Yearling, 2012)
Rosalind heads to the beach when summer arrives, and the rest of the Penderwick girls go to a cozy cottage in Maine with Aunt Claire, leaving Skye feeling slightly overwhelmed with her new role as the oldest available Penderwick.
Sequel to: The Penderwicks on Gardam Street.
Booklist starred
School Library Journal
Wilson's Children
Booklist starred, May 2011
Bulletin (Center for Children's books), July 2011
Keywords: Families -- Maine -- Juvenile fiction; Sisters -- Juvenile fiction; Vacations -- Juvenile fiction; Family life -- Maine -- Fiction; Sisters -- Fiction; Vacations -- Fiction; Family life -- Maine -- Fiction; Sisters -- Fiction; Vacations -- Fiction; Maine -- Juvenile fiction; Maine -- Fiction; Maine -- Fiction